Analysis of Twitter usage in an exploratory seminar setting - Wolfgang Reinhardt; Matthias Moi; Nina Heinze (Firenze University Press, 2013)
Despite the massive social and technological changes that have occurred due to the Web in the recent years, university courses often still emphasize time-honored teaching methods with classical learning tools and resources. During these courses students often acquire knowledge that is not up-to-date and detached from problem-based, realistic learning. The use of more recent tools and methods often remains out of student's grasp. In this article we briefly report on an exploratory seminar setting at two German universities where the use of Social Media for communication and collaboration was firmly embedded in the educational setup. Furthermore, we illustrate the usage of Twitter during the seminar using techniques from Social Network Analysis.